Re-creation After Business Failure: A Conceptual Model of the Mediating Role of Psychological Capital - De Hoe, Roxane; Janssen, Frank (Frontiers in Psychology, 2022)
In case of failure, entrepreneurs could endure various financial, psychological, and social costs. These intertwined costs could affect their learning from failure. All individuals do not react in the same way when dealing with adversity. Rather than focusing on (negative) consequences of business failure, we took a more positive approach by using the Conservation of Resources model theory to build our conceptual model. Psychological capital, which refers to “an individual’s positive psychological state of development characterized by high levels of self-efficacy, optimism, hope and resilience”, could be considered as a resource to recover from entrepreneurial setbacks. We suggest that a high level of psychological capital plays a mediating role in the relationship between the negative consequences of failure and learning from failure. By learning from this experience, failed entrepreneurs will increase their intention to recreate a venture and pursue their entrepreneurial career. This theoretical research, by building a conceptual model based on resources, offers a more positive approach of entrepreneurial failure and investigates key psychological assets, such as psychological capital, that support the development of entrepreneurial resilience rather than the prevention of business failure.